The Effect of Technology Development, Leadership Style and Organization Culture on Employee Performance - Wijaya, Darsyaf Hadi; Eppang, Buntu Maranu (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 2 Tahun 2021, 2021)
This study aims to determine the influence between the development of information technology systems, leadership style, organizational culture, employee performance in the travel industry in South Sulawesi. The survey method approach was used in this study to examine the variables of developing information technology systems that developed with 141 respondents in the travel industry. Determination of the sample using purposive sampling method. The hypothesis was tested using the structural equation modeling (SEM) data analysis method with the help of software, namely Analysis Moment of Structure (AMOS) 20. The results of the discussion of this study explain that: 1) The development of information technology systems has a positive and significant effect on organizational culture. This means that the better the quality of electronic services, the more work culture will increase in the tourism travel industry in South Sulawesi. 2). Leadership style has a positive and significant effect on organizational culture. This means that the higher the level of leadership style, the higher the organizational culture in the travel industry in South Sulawesi. 3). The development of information technology systems has a positive and significant effect on employee performance. This means that the better the quality of electronic services, the more employee performance in the travel industry in South Sulawesi. 4) Leadership style has a positive and significant effect on employee performance. This means that the higher the level of leadership style, the higher the employee's performance in the travel industry in South Sulawesi. 5) Organizational culture has a positive and significant effect on employee performance.